Shopping for Health: Snack Foods - Carley Rusch; Wendy J. Dahl (EDIS, 2015)
At first glance, you might think that snacking should be avoided because of the extra calories they can add to your diet. However, studies have shown there may be benefits when healthy snack choices are made. Read this 4-page fact sheet to learn about the benefits of healthy snacks and to learn healthy snack shopping tips. Includes recipes for homemade crispy kale chips and peanut butter and jelly yogurt. Written by Carley Rusch and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, January 2015. (Photo: iStock/Thinkstock.com)